Comparative Genomic-Based Study of Reproduction-Related Genes in Three Fruit Fly Species - Wu, Yinggu; Lian, Yuyang; Peng, Sihua; Wang, Aqiang; Yang, Heming; Li, Jinlei; Yang, Shuyan; Zhou, Shihao (Frontiers in Genetics, 2022)
Zeugodacus cucurbitae (Coquillett), Bactrocera dorsalis (Hende) and, Ceratitis capitata (Wiedemann) are important pests of fruit and vegetable crops and are difficult to control because of their rapid reproduction rate and egg production. To investigate the key genes regulating reproduction in three fruit fly species, we selected genomic information of three fruit fly species, screened specific genes and single-copy homologs genes, and performed KEGG and GO enrichment analysis on specific genes and single-copy homologs genes of Strong Positive Select (SP), the results showed that Z. cucurbitae (Coquillett), B. dorsalis (Hende) and C. capitata (Wiedemann) had 7, 11 and 1 Vitellogenin- related genes, respectively, Z. cucurbitae (Coquillett) had 84 specific genes enriched in immune system-related pathways, B. dorsalis (Hende) had 1121 specific genes enriched in signaling pathways related to cell growth and differentiation, C. capitata (Wiedemann) had 42 specific genes enriched in degradation and metabolism pathways of exogenous organisms, Z. cucurbitae (Coquillett) may have a stronger immune system, B. dorsalis (Hende) has a faster developmental and reproductive rate, and C. capitata (Wiedemann) has a higher detoxification capacity. Only one SP single-copy homologs gene (gene name: Very long-chain specific acyl-CoA dehydrogenase, mitochondrial) is enriched in the fatty acid metabolic pathway in both Z. cucurbitae (Coquillett) and B. dorsalis (Hende), as well as in Z. cucurbitae (Coquillett) and C. capitata (Wiedemann). This study provides a molecular basis for studying the reproductive mechanisms of three fruit fly species and provides a scientific basis for developing effective control strategies for fruit fly.